Light Metals 2015 2015
DOI: 10.1007/978-3-319-48248-4_187
|View full text |Cite
|
Sign up to set email alerts
|

Description and Applications of a 3D Mathematical Model for Horizontal Anode Baking Furnaces

Abstract: In aluminum industry, carbon anodes are consumed continuously during alumina reduction in the electrolysis cells. Anodes are made of calcined coke, butt, and recycled anode particles and pitch as the binder. Green anodes are baked in large furnaces where they attain specific properties in terms of density, mechanical strength, and electrical conductivity. Baking is an important and costly step in carbon anode production. The proper operation of the furnace provides the required anode quality. Mathematical mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Other studies have explored deformations of geometry. For instance, Baiteche et al [18] studied the effect of flue-wall deformation on anode temperature distribution. Comparing the temperature profiles on a line in the pit transverse direction for straight and deformed flue-walls, it was observed that after flue-wall deformation, the temperature profile is no longer symmetric, which indicates a non-uniform baking process.…”
Section: Related Workmentioning
confidence: 99%
“…Other studies have explored deformations of geometry. For instance, Baiteche et al [18] studied the effect of flue-wall deformation on anode temperature distribution. Comparing the temperature profiles on a line in the pit transverse direction for straight and deformed flue-walls, it was observed that after flue-wall deformation, the temperature profile is no longer symmetric, which indicates a non-uniform baking process.…”
Section: Related Workmentioning
confidence: 99%
“…The anode paste obtained by mixing all the raw materials is compacted in a vibrocompactor to produce green anodes. The green anodes baked in open-pit anode baking furnaces to produce the baked anodes [3][4]. Then, the baked anodes are cooled and rodded before sending them to electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al 34 studied the effects of the bricks arrangements and baffles on the flue flow characteristics of ABF. Baiteche et al 35 studied the temperature profile of anode blocks, and found that due to the flue‐wall deformation, the temperature distribution was no more symmetric with the result of a nonhomogeneity baking process.…”
Section: Introductionmentioning
confidence: 99%